Blended Learning in an Effort to Overcome Learning Materials in Elementary Schools - Suprapto, Irawan; Amriyah, Chairul; Prihatmojo, Agung (Letiges, 2024)
Blended learning is an innovative learning model that integrates relevant technology with learning. This study aims to describe the application of blended learning and its effect on students at the elementary school level as an effort to overcome the risk of falling behind in subject matter after the Covid-19 pandemic. This research uses a case study approach, including qualitative methods. Data collection techniques with interviews, observation and documentation. The analysis technique uses Cresswell analysis. The research results show that the application of blended learning in Sukarno Hatta elementary school is included in several learning models. These models are station rotation models, blog models, online learning, and independent learning. Blended learning can be a valuable alternative for managing student learning at the elementary school level. By utilizing technology and combining various models of approaches, we can overcome the backwardness of learning materials from the effects of changes in the world's education cycle, especially after Covid-19.